Private equity challenge - Calavo growers as a potential lbo target - Ribeiro, Carlos Miguel Abreu (2021)
This Work Project is an individual part of an Investment Committee Paper on Calavo Growers, an American fresh fruit an dhealthyon-the-go fresh food enterprise, developed by a group of Master’s in Finance students. The company is divided in to three segments: Fresh-which handle savocados and other fesh fruits; Calavo Foods–produces processed a vocado products such asgua camole; and RFG–a producer of a portfolio healthy foods such as fresh-cut fruits. This individual part focus on Calavo’s overview as a company, name lyits three segments, its business model, its end markets and its management team. More over, it analyses company’s past financial performance and Covid-19 impact during 2020.